The role of YAP1 in survival prediction, immune modulation, and drug response: A pan-cancer perspective - Hu, Xueqing; Zhang, Yingru; Yu, Hao; Zhao, Yiyang; Sun, Xiaoting; Li, Qi; Wang, Yan (Frontiers in Immunology, 2022)
Introduction Dysregulation of the Hippo signaling pathway has been implicated in multiple pathologies, including cancer, and YAP1 is the major effector of the pathway. In this study, we assessed the role of YAP1 in prognostic value, immunomodulation, and drug response from a pan-cancer perspective. Methods We compared YAP1 expression between normal and cancerous tissues and among different pathologic stages survival analysis and gene set enrichment analysis were performed. Additionally, we performed correlation analyses of YAP1 expression with RNA modification-related gene expression, tumor mutation burden (TMB), microsatellite instability (MSI), immune checkpoint regulator expression, and infiltration of immune cells. Correlations between YAP1 expression and IC50s (half-maximal inhibitory concentrations) of drugs in the CellMiner database were calculated. Results We found that YAP1 was aberrantly expressed in various cancer types and regulated by its DNA methylation and post-transcriptional modifications, particularly m6A methylation. High expression of YAP1 was associated with poor survival outcomes in ACC, BLCA, LGG, LUAD, and PAAD. YAP1 expression was negatively correlated with the infiltration of CD8+ T lymphocytes, CD4+ Th1 cells, T follicular helper cells, NKT cells, and activated NK cells, and positively correlated with the infiltration of myeloid-derived suppressor cells (MDSCs) and cancer-associated fibroblasts (CAFs) in pan-cancer. Higher YAP1 expression showed upregulation of TGF-β signaling, Hedgehog signaling, and KRAS signaling. IC50s of FDA-approved chemotherapeutic drugs capable of inhibiting DNA synthesis, including teniposide, dacarbazine, and doxorubicin, as well as inhibitors of hypoxia-inducible factor, MCL-1, ribonucleotide reductase, and FASN in clinical trials were negatively correlated with YAP1 expression. Discussion In conclusion, YAP1 is aberrantly expressed in various cancer types and regulated by its DNA methylation and post-transcriptional modifications. High expression of YAP1 is associated with poor survival outcomes in certain cancer types. YAP1 may promote tumor progression through immunosuppression, particularly by suppressing the infiltration of CD8+ T lymphocytes, CD4+ Th1 cells, T follicular helper cells, NKT cells, and activated NK cells, as well as recruiting MDSCs and CAFs in pan-cancer. The tumor-promoting activity of YAP1 is attributed to the activation of TGF-β, Hedgehog, and KRAS signaling pathways. AZD2858 and varlitinib might be effective in cancer patients with high YAP1 expression.